2015
DOI: 10.1095/biolreprod.114.125674
|View full text |Cite
|
Sign up to set email alerts
|

The Catecholestrogen, 2-Hydroxyestradiol-17beta, Acts as a G Protein-Coupled Estrogen Receptor 1 (GPER/GPR30) Antagonist to Promote the Resumption of Meiosis in Zebrafish Oocytes1

Abstract: Estradiol-17beta (E2) maintains high cAMP levels and meiotic arrest in zebrafish oocytes through activation of G protein-coupled estrogen receptor (GPER). The catecholestrogen 2-hydroxyestradiol-17beta (2-OHE2) has an opposite effect to that of E2 on oocyte maturation (OM) and cAMP levels in Indian catfish oocytes. We tested the hypothesis that 2-OHE2 is produced in zebrafish ovaries and promotes the resumption of oocyte meiosis through its action as a GPER antagonist. Ovarian 2-OHE2 production by estrogen-2-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
(95 reference statements)
0
17
0
Order By: Relevance
“…Previously, treatment of Atlantic croaker ovarian membranes by GPER agonist has been shown to increase Ac activity and also reversed the downregulation of Ac activity by 20b-S (Pang et al 2008). While stimulation with catecholestrogen has been shown to down-regulate intra-oocyte cAMP level (Chourasia et al 2015), MIS action, presumably through mPRa, attenuates Ac activity and intra-oocyte cAMP level by activating the inhibitory G protein, Ga i (Zhu et al 2003). Earlier we have reported that PI3K/Akt pathway is indispensable for insulin-induced meiotic maturation in denuded zebrafish oocyte, where PDE3 might act as possible a down-stream target (Das et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, treatment of Atlantic croaker ovarian membranes by GPER agonist has been shown to increase Ac activity and also reversed the downregulation of Ac activity by 20b-S (Pang et al 2008). While stimulation with catecholestrogen has been shown to down-regulate intra-oocyte cAMP level (Chourasia et al 2015), MIS action, presumably through mPRa, attenuates Ac activity and intra-oocyte cAMP level by activating the inhibitory G protein, Ga i (Zhu et al 2003). Earlier we have reported that PI3K/Akt pathway is indispensable for insulin-induced meiotic maturation in denuded zebrafish oocyte, where PDE3 might act as possible a down-stream target (Das et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in epidermal growth factor receptor (Egfr) transactivation and MAPK activation, studies in Atlantic croaker and zebrafish oocytes have indicated that binding of E 2 to its novel G-protein coupled membrane receptor Gper, promotes intra-oocyte adenylate cyclase activity and ensures prophase-I arrest (Pang et al 2008, Peyton & Thomas 2011. Further, recent evidence demonstrates that catecholestrogen (17b-2-hydroxyestradiol) functions as a Gper antagonist and promotes GVBD response in zebrafish by blocking Gper-dependent E 2 action (Chourasia et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2-MeO-E2 has been investigated clinically under the trade name Panzem (EntreMed, Inc., Rockville, MD) for ovarian cancer and other indications (Verenich and Gerk, 2010). In addition, 2-hydroxyestradiol has recently been shown to act as a GPER antagonist, acting to promote the resumption of meiosis in zebrafish oocytes, with a binding affinity in the range of 0.1-1 mM (Chourasia et al, 2015). The GPER binding of the other oxidized E2 metabolites 4-hydroxy-E2 and 4-methoxy-E2 has not been reported.…”
Section: B Steroidsmentioning
confidence: 99%
“…Rather, it has been found recently that E2 - via ERα - inhibits mineralocorticoid receptor (MR) function [29]. Natural estrogen metabolites formed by catchol-O-methyltransferase, have recently been shown to bind to and signal through GPER, either as an agonist (2-methoxyestradiol, 2-ME2) [30], or antagonist (2-hydroxy estradiol (2-OH-E2) – a hydroxylated metabolite of E2) [31] (Figure 1). Furthermore, a large number of synthetic and natural estrogenic compounds have been shown to interact with GPER (Figure 1), including the therapeutic anti-estrogens ICI182,780 (a selective ER downregulator, SERD) and 4-hydroxytamoxifen and raloxifene (selective ER modulators, SERMs), which surprisingly all act as GPER agonists [13, 32, 33], and synthetic compounds such as MIBE (ethyl 3-[5-(2-ethoxycarbonyl-1-methylvinyloxy)-1-methyl-1H-indol-3-yl]but-2-enoate)) [34].…”
Section: An Intracellular G Protein-coupled Membrane Estrogen Receptormentioning
confidence: 99%